Arakabu and the Arakawa Mountain Kami - Foster, JC (Anthropological Society of Oxford, 2014)
Under the assumption that religious concepts are like any other concepts, ethnographic studies have been able to provide plausible explanations for a wide range of religious beliefs and behaviour. One under-studied question asks how such concepts help form specific expectations about social life in modern communities. Here, we focus on how a micro-community in a southern Japanese village edits inherited religious concepts to help make solutions to a social problem intelligible. In section one, we study the variables: the religious concept, the problem, and the micro-community. In section two we turn to the details of the editing of the concept.